Geophysikalische Prospektion und magnetische Eigenschaften von ausgewählten Böden der Osterinsel - Fassbinder, Jörg W. E.; Bondar, Ksenija (Zeitschrift für Archäologie Außereuropäischer Kulturen, 2023)
It was a widely held belief that the search for archaeological structures by magnetometer prospection on volcanic soils developed on basaltic geology is utterly impossible because of the intensive magnetic background of the geological structures. The primary aim of this research project was therefore to undertake a series of measurement by the total fi eld caesium magnetometer and by a resistivity meter on archaeological sites on the Island. For a entire understanding and complemented interpretation of the resulting magnetogramms a detailed analysis of the rock magnetic properties of typical soils on Easter Island was performed on samples of a remaining soil profi le of a quarry, as well as on selected top soil samples from different archaeological sites. In situ measurements of the magnetic volume susceptibility revealed already the enrichment of magnetic minerals in the top soils. This finding encouraged us to undertake a series of test measurement on archaeological sites to trace archaeological structures with the magnetometer. In total eight areas in the front and adjacent to the visible ruins of the Ahus were choosen as archaeological test sites. The results show that we were able to detect and to interpret a large range of archaeological features beneath the ground that were not visible and not known before. All these geophysical results are non-destructive and were done without excavation and touching the ground. The geophysical prospecting methods as well as the soil magnetic analysis is thus an excellent tool to recover and to understand further archaeological details and contribute to the appreciation of these extraordinary monuments. It will also help archaeologist to reduce scientifi c excavations to small size or trenches, which will help to preserve archaeological sites.Der Artikel wird zeitnah als PDF verfügbar sein.